Gender disparities in depressive and anxiety symptoms among internal migrant workers in Shenzhen: a cross-sectional study - Fengsu Hou; Huiming Liu; Xiaodong Peng; Liqin You; Zhijian Zhou; Haiyan Xie; Tiebang Liu (BMJ Open)
Objectives To investigate the gender disparities in the prevalence and severity of depressive and anxiety symptoms and associated factors among internal migrant workers in Shenzhen.Design Cross-sectional study.Setting Labour intensive factories in Shenzhen, Guangdong, China.Participants We recruited 3200 internal migrant workers who aged over 18 years old and above and did not register in Shenzhen’s household registration system. There were 3095 participants eligible for this study.Methods Participants completed sociodemographic questionnaire, the Patient Health Questionnaire-9, the Generalized Anxiety Disorder-7, the UCLA Loneliness Scale, the Barratt Impulsiveness Scale, the Social Support Rating Scale, the Simplified Coping Style Questionnaire and Meaning in Life Questionnaire. We applied χ2 test, analysis of variance, Wilcoxon rank test, Fisher’s exact test and univariate and multivariate multilevel linear regression analysis.Results The overall prevalence of depressive and anxiety symptoms was 27.85% and 19.26% among internal migrant workers. We reported gender disparities of depressive and anxiety symptoms among participants that the prevalence of depressive and anxiety symptoms was higher in women (30.57% vs 26.43% and 22.67% vs 17.47%), and the symptoms were more severe among women. Female migrant workers were more likely to be singled, have lower prevalence of smoking and drinking, receive less education and monthly income, have higher level of impulsiveness and social support and lower level of meaning in life. We found age, marriage, income, adaption to living in Shenzhen, being discriminated, drinking, loneliness, impulsiveness, social support, coping strategies and meaning of life were associated with the severity of depressive and anxiety symptoms among internal migrant workers in Shenzhen.Conclusion Gender inequality may be the institutional factor leading to disparities in depressive and anxiety symptoms among internal migrant workers. Interventions should be embedded with strategies improving gender equality.